Wheat Improvement, Management and Utilization 2017
DOI: 10.5772/67246
|View full text |Cite
|
Sign up to set email alerts
|

Grading Factors of Wheat Kernels Based on Their Physical Properties

Abstract: Cereal grains are biological materials and as such have certain unique characteristics greatly affected by both genetics and environment. Wheat is worldwide considered as the main cereal grain in the average human diet. The aim of this chapter is to provide an overview of the most important grading factors and kernel physical parameters that are involved in the estimation of quality specifications. The determination of the physical properties of wheat kernels gives a first approximation of the structural chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Such properties affect kernel selection by sieve separators and the estimated extraction rate during size reduction processes. The axial dimensions of kernels are essential for calculating the kernel volume for modeling drying, aeration, heating, and cooling [10]. The results of this study showed that the axial dimensions of the three cereal types corresponded to optimal values reported in other studies, which can be used to produce specific food products.…”
Section: Biophysical Propertiessupporting
confidence: 63%
See 2 more Smart Citations
“…Such properties affect kernel selection by sieve separators and the estimated extraction rate during size reduction processes. The axial dimensions of kernels are essential for calculating the kernel volume for modeling drying, aeration, heating, and cooling [10]. The results of this study showed that the axial dimensions of the three cereal types corresponded to optimal values reported in other studies, which can be used to produce specific food products.…”
Section: Biophysical Propertiessupporting
confidence: 63%
“…Gómez et al [4] demonstrated that the starch structure, enzyme content (amylases), and other soluble components of the pericarp have important effects on the rheological properties of rye dough during the bread-making process. In previous studies, some mechanical and viscoelastic properties of kernels showed a significant correlation with the dough performance and quality of bakery products [10,37]. The bread-making process is very complex, and it involves mixing, sheeting, fermentation, and baking in the oven.…”
Section: Mechanical and Viscoelastic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation